Pengembangan Model Pembelajaran Integratif Berbasis Nilai Moderasi Beragama pada Pembelajaran PAI dan Budi Pekerti di SMA - Fadriati Fadriati; Yuliana Putri; Abdul Razzak Yoma; Rinda Rohayu (IAIN Batusangkar, 2024)
This research is motivated by global progress which has a positive impact on modernization in various aspects of life. To make students can understand and apply the values of religious moderation in everyday life, this research aims to integrate these values into the Islamic religious education learning model. Through teaching and learning activities in classroom, this approach can help students develop an understanding of religious moderation in everyday life. Therefore, this research needs to be carried out to determine the validity and practicality of the Integrative Learning Model Based on Religious Moderation Values in Islamic Education and Character Learning in High School. This research used ADDIE as the development model with 5 stages namely Analysis, Design, Development, Implementation and Evaluation. The data sources were practicality and validity sheet, interview and documentation study. The research results showed that the validity of the integrative learning model book was 0.88 in highly valid category and the practicality of the integrative learning model book was 0.85 in highly valid category. The results of this research described that a learning model book that combines the values of religious moderation in Islamic Education and Character Learning subjects is very suitable to be used in learning process.